The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1091/mbc.e15-06-0408
|View full text |Cite
|
Sign up to set email alerts
|

The complex genetic and molecular basis of a model quantitative trait

Abstract: Sixty‐four genomic loci and seven genes that contribute to heritable variation in a model quantitative trait—resistance to oxidative stress—are identified across three yeast strains. The high‐resolution understanding of this phenotype provides new insight into the genetic and molecular basis of quantitative traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Based on the X‐QTL mapping results, we used an approach previously applied to yeast (Linder et al . ) and plotted the allele count for each SNP across the genomic regions associated with germination speed QTLs on chromosomes 1, 3 and 4 (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the X‐QTL mapping results, we used an approach previously applied to yeast (Linder et al . ) and plotted the allele count for each SNP across the genomic regions associated with germination speed QTLs on chromosomes 1, 3 and 4 (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Even the nonsignificant region on chromosome 3 displayed a 10% allele frequency shift towards the early-germination Bs-2 allele. Based on the X-QTL mapping results, we used an approach previously applied to yeast (Linder et al 2016) and plotted the allele count for each SNP across the genomic regions associated with germination speed QTLs on chromosomes 1, 3 and 4 (Fig. 6).…”
Section: Germination Speed X-qtls Confirmed By Sequencing Individual mentioning
confidence: 99%
“…In model organisms, the hunt for causative, naturally-segregating variation commonly begins with linkage-based QTL (quantitative trait locus) mapping. Whether initiated with two parental strains (LANDER AND BOTSTEIN 1989), or more recently with several founders (KOVER et al 2009;CHURCHILL et al 2012;KING et al 2012b; THREADGILL AND CHURCHILL 2012), such mapping designs have tremendous power to find QTL, and in some cases have led to the identification of specific polymorphisms contributing to complex trait variation (e.g., LONG et al 6 2000; DEUTSCHBAUER AND DAVIS 2005;BENDESKY et al 2011;COOK et al 2016;LINDER et al 2016). These variants facilitate a deeper understanding of specific biomedically-relevant traits, and collectively add to a fundamental appreciation of complex trait variation and its maintenance in populations.…”
Section: Introductionmentioning
confidence: 99%
“…While we found no significant QTLs for basal H 2 O 2 resistance, we did find a significant QTL peak on chromosome XII for cross protection (Fig 2). It is unlikely that our failure to detect a chromosome XII QTL for basal H 2 O 2 resistance was due to a lack of statistical power, because two independent basal H 2 O 2 resistance QTL studies using millions of S288c x YPS163 F 2 segregants also found no significant associations at this locus [69,70]. Additionally, we estimated the heritability of phenotypic variation in basal resistance to be 0.79, which is slightly above the median value estimated by Bloom and colleagues for 46 yeast traits [71], and is only moderately lower than the heritability for cross protection (0.92).…”
Section: The Genetic Basis Of Natural Variation In Yeast Cross Protecmentioning
confidence: 91%